Electronic cigarette use and smoking reduction – longitudinal data from CONSTANCES cohort study. (13th November 2019) - Gomajee, R; El-Khoury, F; Goldberg, M; Zins, M; Lemogne, C; Wiernik, E; Lequy-Flahault, E; Romanello, L; Kousignian, I; Melchior, M
Abstract: Aims: Electronic cigarettes are often used by smokers to stop smoking and former smokers to prevent relapse. We examined whether electronic cigarette use lead to smoking reduction and cessation among smokers, and relapse among former smokers. Design and Settings: The CONSTANCES cohort, France (2012 - ongoing). Measurements: Among smokers (N = 5, 400, average follow-up of 23.4 months), mixed regression models were used to examine whether electronic cigarette use was linked to a decrease in the number of cigarettes smoked per day and Poisson regression models with sandwich variance estimators were used to test smoking cessation. In parallel, Cox proportional hazards regression models were used to examine the relationship between electronic cigarettes use and smoking relapse among former smokers who stopped smoking since 2010 (N = 2, 025, average follow-up of 22.1 months), year in which electronic cigarettes were introduced in France. All statistical analyses were adjusted for socio-demographic characteristics, duration of follow-up, and smoking characteristics. Findings: There was a significantly higher decrease in the number of cigarettes smoked/day among smokers who used electronic cigarettes (decrease of 4.4 cigarettes/day) compared to those who did not (decrease of 2.7 cigarettes/day), as well as a higher relative risk of smoking cessation (adjusted RR: 1.67 [95% CI: 1.51-1.84]). At the same time, among former smokers, EC use was associated with an increase in the rate of smoking relapse (adjusted HR = 1.70 [95% CI: 1.25-2.30]). Conclusions: After a follow-up of approximately 2 years, electronic cigarettes use among smokers was associated to a decrease in smoking level and an increase in smoking cessation attempts but among former smokers it was associated to a higher risk of smoking relapse. Key messages: Among smokers, electronic cigarette use was associated to smoking reduction and smoking cessation. Among former smokers who quit smoking since 2010, electronic cigarette use was associated to a higher likelihood of relapse.